Dietary incorporation of melittin and clove essential oil enhances performance, egg quality, antioxidant status, gut microbiota, and MUC-2 gene expression in laying hens under heat stress conditions - Ahmed M. Elbaz; Ahmed S. El-Hawy; Fayza M. Salem; Maha F. Lotfy; Ahmed Ateya; Garsa Alshehry; Youssef S. Alghamdi; Mohamed E. Abd El-Hack; Ahmed A. Elolimy; AbdelRahman Y. Abdelhady (Italian Journal of Animal Science)
High environmental temperatures can severely impact poultry performance, leading to economic losses and compromised bird welfare. This study evaluated the effects of dietary supplementation with melittin and clove essential oil—individually or in combination—on laying hens exposed to heat stress. A total of 216 Brown Lohmann hens (25 weeks old) were randomly distributed in a completely randomised design into four groups and followed for 15 weeks. Birds received either a basal diet or the same diet supplemented with melittin (150 mg/kg), clove essential oil (300 mg/kg), or both. The combination treatment (ACC) significantly improved hen-day egg production (HDEP), egg weight, egg mass and feed conversion ratio. Egg quality traits such as shell strength, thickness, albumen weight and height were also enhanced. Moreover, ACC supplementation boosted nutrient digestibility, particularly for protein and fibre. Physiological indicators showed improved antioxidant status, with higher superoxide dismutase and lower malondialdehyde levels. Triiodothyronine (T3) levels increased, while corticosterone levels declined, indicating better stress adaptation. Gut microbiota analysis revealed a rise in Lactobacillus counts and a reduction in pathogenic bacteria. Additionally, MUC-2 gene expression was upregulated, supporting gut barrier integrity. These results highlight the potential of combining melittin and clove essential oil in layer diets as a natural strategy to counteract the negative impacts of heat stress.